A second monoclinic polymorph of ethylenediammonium bis(hydrogen squarate) monohydrate - Louiza Zenkhri; Thierry Bataille; Nathalie Audebrand (Acta Crystallographica Section E, 2011)
The title compound, C2H10N22+·2HC4O4−·H2O, a new polymorph of ethylenediammonium bis(hydrogen squarate) monohydrate, was synthesized by slow evaporation of an acid solution. The asymetric unit contains two hydrogen squarate anions, two half-molecules of protonated ethylenediamine arranged around a twofold axis and one water molecule. In the crystal, N—H...O and O—H...O hydrogen bonds between the hydrogen squarate anions, protonated N atoms from the amine group and water molecules lead to a three-dimensional framework. In particular, the cohesion between the squarate groups is ensured by very short intermolecular hydrogen bonds bonds. The title compound crystallized together with the previously reported polymorph [Mathew et al. (2002). J. Mol. Struct. 641, 263–279].